A geometria na arquitetura : uma abordagem dos estilos arquitetônicos da Antiquidade Clássica, do Renascimento e da Modernidade - Santos, Marcia Boiko dos (2013)
The perception of the intrinsic relationship between Space Art (Architecture) and Space Science (Geometry) is a factor that stimulated the interest in this theme, such as the way to study Geometry in the Basic Education System, in a more fascinating and pleasurable way, giving a different focus to the method ofteaching. For this purpose tlirough the study of some geometric concepts and esthetical qualities of Architecture, showing possible relationships between these two areas of knowledge in tbree relevant periods of history. That is: In a Classical Antiquity Period under the geometrie viewpoints, the relation of Symmetry and Proportions in the Greek buildings was noticed, as well the Romans with the retum of the Accord "De Architetura" of Vitruvio; In a Renaissance Period the emphasis on Perspective, with a focus on Leonardo Da Vinci, Filippo Brunelleschi and Leon Battista Alberti and finally in a Modernity Period the utility of Topology with emphasis on the works of Oscar Niemeyer was analysed. The main objective was to verif,i the contributions that the works of these artists architecture can provide to the method ofteaching with geometric concepts in the Basic Education System in the present time. Prioritized resource in images, where the objective to make possible the expansion of the skills of visualization and interpretation in some developed technology in distinct periods of history. In this context, therefore, this work was conducted qualitative and documentary research oftheory and epistemological by cleat, that is the investigated point ofcontacts between these two areas of knowledge.